The Dynamics Of The Traditional Economic Dynamics Of The South Tapanuli Community In The Current Modernization Era - Replita, Replita; Effendi, Nursyirwan; Ophiyandri, Taufika; Miko, Alfan (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2025)
Traditional markets in South Tapanuli have an important role in driving people's economic activities, but the modernization and dominance of the modern retail market poses challenges to the sustainability of the local economy. The background of the problems in this study includes the decline in the competitiveness of traditional markets, changes in people's consumption patterns, and limited facilities and policy support. This research aims to analyze the contribution of traditional markets to the sustainable welfare of the local economy, including aspects of traders' income, community involvement, and regional economic turnover. The research method uses a qualitative approach with field studies in several key markets in South Tapanuli, through in-depth interviews with traders, market managers, and consumers, as well as direct observation of trading activities. The results of the study show that traditional markets remain the center of economic and social interaction, able to increase the income of small traders, and become a forum for the distribution of local products that boost the regional economy. However, the sustainability of traditional markets requires improving the quality of facilities, strengthening management, and government policy support to increase competitiveness. This research confirms that traditional markets have a strategic role in maintaining the sustainability of the local economy in South Tapanuli.